HYDRODYNAMICS AND MORPHOLOGY CHANGES STUDIES OF SEGARA ANAKAN - Hariati, Feril
The lagoon is a very dynamic coastal water. Coastal lagoons are estimated to occupy 13% of the coastlines in the world. Segara Anakan Lagoon is the largest coastal lagoon system on the south coast of Java Island and the estuary for three major rivers; Citanduy, Cibeureum, and Cikonde. The lagoon faces surface water’s shrinkage due to the sedimentation process which formed accretion islands in the central part of the lagoon. Since the lagoon’s water is fertile, the shrinkage of the lagoon water will threaten the food security of the nation. The accretion islands narrowed the channel; thus, the Nusakambangan Island, the barrier island of the lagoon where the high-security prison is located, is becoming more accessible from the mainland. Tides and river flow are the main drivers of the hydrodynamics of Segara Anakan Lagoon. The Citanduy river supplies about 80% of the freshwater to the lagoon. It also brings the sediments from the land erosion process due to land cover change in the watershed. Applying the USLE method, the land erosion rate per year from 2005 to 2016 was obtained. The number of sediments that enter the lagoon was about 3 tons/ha per year or equivalent to 385.440 m3 per year. As a result, the growth of accretion islands reaches ± 9,0 ha per year. Spatial analysis studies of lagoon morphology changes, using maps and satellite imagery from 1942, 1978, 1996, and 2017 showed that the morphology changes of the lagoon are very dynamic. Decreasing the surface area of the lagoon’s water is primarily caused by the increase of the accretion island area in the middle of the lagoon. In the dry season, the area of the accretion island increases, while in the wet season, the islands tend to be eroded. Based on Landsat imagery observations of the land cover of accretion islands, the dominant type of vegetation is mangroves. A model of the lagoon hydrodynamic was set up with a numerical model approach to determine the tidal current and salinity distribution patterns in the lagoon, seawater intrusion in rivers that supply fresh water to the lagoon, and the impact of morphological changes on current velocity and direction patterns, and their effect on sedimentation process. The hydrodynamic of the lagoon is influenced by 1. the tides of the Indian Ocean waters, with mixed semi-diurnal tidal types. Water slack during spring tide, neap tide, and daily tide, respectively, are 2,09 m, 0,75 m, and 1,39 m. With a tidal height is less than 2,0 m, Segara Anakan Lagoon is categorized as a microtidal lagoon that has very abundant biodiversity. The lagoon is river-dominated. The Citanduy River is the main driver of water circulation in the lagoon. Freshwater supply from the Citanduy River is an important factor in maintaining the salinity of lagoon waters. The salinity of brackish water is about 0,5 ppt to 30 ppt. The Segara Anakan Lagoon is brackish water all the time, with the lowest salinity during the wet season being about 3,0 ppt and in the dry season at 29 ppt. The horizontal salinity gradient of the lagoon waters from the area nearest the West Plawangan inlet to the lagoon waters in the northeastern part is close to zero. There is no horizontal stratification in the waters of the lagoon. Morphological changes do not affect the pattern of salinity distribution in lagoon waters. The salinity of the lagoon waters is brackish waters for any morphology. The morphology of 1942 was the ideal condition, with salinity values not exceeding 25 ppt. As the salinity of the lagoon waters is high, the intrusion of seawater into the rivers becomes longer in the upstream direction. The morphology of 1942 resulted in the length of intrusion in the Citanduy River reaching 4 km during the dry season. For the morphology of 1978, 1996, and 2017, the intrusion length reached 16 km in an upstream direction. In the Cibeureum and Cikonde Rivers, seawater intrusion reaches 7 km and 4 km upstream, with a maximum salinity of upstream reaching 25 ppt and tends to be the same for each morphological condition. Previous studies showed that salinity increased the settling velocity of clay and silt. Lagoon’s water usually calms with salinity between 0.5 ppt to 30 ppt and makes it a potential location for sediments to settle down. The evaluation of the hydrodynamics of the lagoon before and after the formation of accretion islands in the central zone of the lagoon is carried out by defining Models A and B. Model A is the condition before the accretion island is formed, while model B is after the accretion island is formed. Model A was a natural condition of the lagoon. The current velocity in the central lagoon zone to the northeastern varied between 0,0018 m/s to 0,35m/s. In the wet season, the river discharge could reach 400 m3/s. The flow velocity of the river was higher than 0,35 m/s, which is the velocity limit for sediment starting to erode. The eroded sediments were carried into the central lagoon zone and moved with the water to the eastern and northeastern zone of the lagoon. In the dry season, the current speed in the middle zone of the lagoon was lower than 0,0018 m/s and the salinity value was getting higher. Since the current velocity can no longer move the sediments, they will be deposited at the bottom of the lagoon. The processes of sediment transport and deposition continue. The accumulation of sediment deposition then formed accretion islands. The hydrodynamics of the lagoon was changed due to its morphology change. In the wet season, the current velocity of the central lagoon could be higher than 0,35 m/s, especially in the small channels between the islands. Accretion islands were 1. eroded, and sediments were transported to the eastern zone, where the current velocity was almost zero. In the dry season, the current velocity decreased while the salinity of the waters increased. A sedimentation process occurs. The erosion and accretion process continues, which could keep the morphology of the lagoon open.